Karakteristik Polisakarida Larut Air Umbi Gembili dan Umbi Dahlia serta Aplikasinya Pada Produk Pangan: Review - Witoyo, Jatmiko E; Permatasari, Nelsy D; Rahayu, Lisa F; Utoro, Panggulu A R; Saraswati, Ayu R (AGRITEKNO: Jurnal Teknologi Pertanian, 2025)
Local roots and tubers represent part of Indonesia’s rich biodiversity and are known for their high water-soluble polysaccharide (WSP) content. Dioscorea esculenta and Dahlia sp. tubers are notable examples that have attracted interest due to their WSP composition and potential application in a wide range of food products. However, the physicochemical properties of WSP derived from Dioscorea esculenta and Dahlia sp. tubers, as well as their applications in various food products, remain underexplored. Therefore, this review aims to provide a comprehensive understanding of the physicochemical characteristics of WSP from Dioscorea esculenta and Dahlia sp. Tubers and to highlight their potential uses in food products through a narrative literature review (NLR). The literature study indicates that the WSP present in Dioscorea esculenta tuber includes inulin and glucomannan, while Dahlia sp. tuber contains primarily inulin. WSP from both tubers exhibit unique characteristics and offer multiple functionalities, including use as thickeners, dietary fiber enhancers, prebiotics, fat and sugar replacers, texture modifiers, and emulsifiers. These attributes enable their application in a variety of food products, such as cookies, ice cream, sweet bread, chicken sausages, and kefir.